2006
DOI: 10.1002/ajim.20406
|View full text |Cite
|
Sign up to set email alerts
|

Airway disease in highway and tunnel construction workers exposed to silica

Abstract: Tunnel construction workers exposed to respirable crystalline silica and cement dust are at increased risk for airway disease. Extent of risk varies by trade and work activity. Our data indicate the importance of bystander exposures and suggest that tunnel jacking may be associated with greater risk compared to more traditional methods of tunnel construction. A healthy worker effect is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…A similar result was found in the study of Oliver and Miracle-McMahill (2006) considering highway and tunnel construction workers exposed to silica. They too observed a signiWcant inverse trend for number of months on the contract site and respiratory outcome (symptoms consistent with asthma, chronic bronchitis, and shortness of breath).…”
Section: Discussionsupporting
confidence: 89%
“…A similar result was found in the study of Oliver and Miracle-McMahill (2006) considering highway and tunnel construction workers exposed to silica. They too observed a signiWcant inverse trend for number of months on the contract site and respiratory outcome (symptoms consistent with asthma, chronic bronchitis, and shortness of breath).…”
Section: Discussionsupporting
confidence: 89%
“…In their review Hnizdo and Vallyathan [2003] concluded that exposure to levels of silica dust not expected to cause disabling silicosis may cause chronic bronchitis, emphysema, and/or small airways disease. Much of this evidence has come from studies of mining and milling and mineral processing populations; however, increased airways disease has been observed among construction workers doing highway and tunnel work and exposed to silica [Oliver and Misracle-McMahill, 2006]. Consistent with our results, a number of studies have found significantly increased risk of COPD among welders and other workers performing welding tasks [Mastrangelo et al, 2003;Meldrum et al, 2004;Balmes, 2005;Hunting and Welch, 1993].…”
Section: Discussionsupporting
confidence: 88%
“…Whereas there are no disparities in smoking cessation attempts by occupational grouping, disparities exist in success with smoking cessation whereby blue-collar workers are less likely to quit successfully [Barbeau, et al 2004, Giovino, et al 2000, Nelson, et al 1994]. This persistent disparity, along with evidence that blue-collar workers are more likely to experience occupational exposure to other carcinogens [Meeker, et al 2006, Oliver and Miracle-McMahill 2006, Rappaport, et al 2003, Sorensen, et al 1996], makes it necessary to identify elements of smoking cessation interventions that are efficacious for blue-collar workers.…”
Section: Introductionmentioning
confidence: 99%